Reading Traits for Dynamically Presented Texts: Comparison of the Optimum Reading Rates of Dynamic Text Presentation and the Reading Rates of Static Text Presentation - Uetsuki, Miki; Watanabe, Junji; Ando, Hideyuki; Maruya, Kazushi (Frontiers in Psychology, 2017)
With the growth in digital display technologies, dynamic text presentation is used widely in everyday life, such as in electric advertisements and tickers on TV programs. Unlike static text reading, little is known about the basic characteristics underlying reading dynamically presented texts. Two experiments were performed to investigate this. Experiment 1 examined the optimum rate of dynamic text presentation in terms of a readability and favorability. This experiment demonstrated that, when the rate of text presentation was changed, there was an optimum presentation rate (around six letters/sec in our condition) regardless of difficulty level. This indicates that the presentation rate of dynamic texts can affect the impression of reading. In Experiment 2, to elucidate the traits underlying dynamic text reading, we measured the reading speeds of silent and trace reading among the same participants and compared them with the optimum presentation rate obtained in Experiment 1. The results showed that the optimum rate was slower than with silent reading and faster than with trace reading, and, interestingly, the individual optimum rates of dynamic text presentation were correlated with the speeds of both silent and trace reading. In other words, the readers who preferred a fast rate in dynamic text presentation would also have a high reading speed for silent and trace reading.